De-epithelialised fasciocutaneous turnover flap: An alternative for defects in lower thigh and knee joint - Sharma R; Nanda Vipul; Makkar Surinder; Parasher Atul (Indian Journal of Plastic Surgery)
We describe the use of proximally based de-epithelialised fasciocutaneous flap for coverage of defects in the lower thigh and knee joint. These flaps are based on a number of perforators around the knee joint and can be based either posteriorly, posteromedially or posterolaterally depending upon the location of the defect. The whole of the flap including the bridge segment is de-epithelialised and turned over by 180 degrees and a split thickness graft is placed over the flap and the donor site. The flaps can be raised quickly, have minimum morbidity and are reliable even in the presence of extensive injuries. These flaps have remained stable and trouble free during a follow up period of 2-4 years.